We have to determine a-bi if (2-i)(a-bi) = 2+9i

(2-i)(a-bi) = 2+9i

=> 2a - 2bi - ai + bi^2 = 2 + 9i

=> 2a - b - 2bi - ai = 2 + 9i

Equating the real and imaginary coefficients we get

2a - b = 2 and...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

We have to determine a-bi if (2-i)(a-bi) = 2+9i

(2-i)(a-bi) = 2+9i

=> 2a - 2bi - ai + bi^2 = 2 + 9i

=> 2a - b - 2bi - ai = 2 + 9i

Equating the real and imaginary coefficients we get

2a - b = 2 and 2b + a = -9

=> 2(-2b - 9) - b = 2

=> -4b - 18 - b = 2

=> -5b = 20

=> b = -4

a = 8 - 9 = -1

**The required number a + bi = -1 - 4i**